2003
DOI: 10.1029/2003jd003798
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of mineral dust outbreaks over the northeastern Mediterranean

Abstract: 1] Ground-based aerosol optical measurements were conducted within the framework of the Aerosol Robotic Network (AERONET) program at the IMS-METU site at Erdemli (36°33 0 N, 34°15 0 E) along the Turkish coast of the northeastern Mediterranean from January 2000 to June 2001. The measurements were used to identify and define predominant regional aerosol optical properties, with an emphasis on mineral dust intrusion events. Dust storms affecting the region primarily originate from the central Sahara in spring, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
109
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(120 citation statements)
references
References 53 publications
10
109
0
1
Order By: Relevance
“…At local scale (geographical distributions), among the studied cases, in areas where the desert dust outbreaks' intensity is maximized, the SH fluxes are reduced by up to 150 W m −2 during day-time and increased by up to 50 W m −2 during night-time. Our findings are consistent with those presented by Mallet et al (2009) and Rémy et al (2015), who analysed the impact of dust storms on sensible heat fluxes over western Africa and Mediterranean, respectively, and substantially higher than the instantaneous perturbations of SH calculated by Kumar et al (2014), who studied a dust outbreak that occurred in northern India (17-22 April 2010).…”
Section: Impact On Sensible and Latent Heat Fluxessupporting
confidence: 82%
See 3 more Smart Citations
“…At local scale (geographical distributions), among the studied cases, in areas where the desert dust outbreaks' intensity is maximized, the SH fluxes are reduced by up to 150 W m −2 during day-time and increased by up to 50 W m −2 during night-time. Our findings are consistent with those presented by Mallet et al (2009) and Rémy et al (2015), who analysed the impact of dust storms on sensible heat fluxes over western Africa and Mediterranean, respectively, and substantially higher than the instantaneous perturbations of SH calculated by Kumar et al (2014), who studied a dust outbreak that occurred in northern India (17-22 April 2010).…”
Section: Impact On Sensible and Latent Heat Fluxessupporting
confidence: 82%
“…Subsequently, variations of SH and LE have an impact on the components of the hydrological cycle (Miller et al, 2004b) as well as on the turbulent kinetic energy and momentum transfer which in turn affect near-surface winds and dust emission (Pérez et al, 2006). Moreover, Marcella and Eltahir (2014) and Kumar et al (2014) have shown that due to the presence of dust aerosols in the atmosphere, the day-time surface sensible heat fluxes are reduced, leading to a reduction in the planetary boundary layer (PBL) height.…”
Section: Impact On Sensible and Latent Heat Fluxesmentioning
confidence: 99%
See 2 more Smart Citations
“…Three main trajectories of dust from the Saharan source area are distinguished ). The first is over thousands of kilometres and crosses the Atlantic Ocean to the United States, the Caribbean and South America (Chiapello et al 1995;Kellogg et al 2004); the second carries dust to the Mediterranean and Europe (Kellogg et al 2004;Perez et al 2008); and the third transports dust to the eastern Mediterranean and the Middle East (Kubilay et al 2003;Middleton et al 2008). Each of these trajectories can be seen at a specific period of the year, with intensity varying annually .…”
Section: Dust-health Relationship -Publication Datementioning
confidence: 99%